Psychosocial Factors Associated with Healthy and Unhealthy Interpregnancy Intervals - Ruth Young; Wendy G. Lane; Wendy G. Lane; Stacey B. Stephens; Bronwyn W. Mayden; Renee E. Fox (Mary Ann Liebert, 2018)
Purpose: To examine the influence of psychosocial factors, including anxiety, depression, social support, maternal substance abuse, and intimate partner violence (IPV) on interpregnancy intervals (IPIs). Methods: B'more for Healthy Babies?Upton/Druid Heights is part of a citywide initiative to improve the health of at-risk pregnant women and their children. Participants with at least one prior birth completed baseline, postpartum, and 3-month follow-up surveys with questions about pregnancy, medical, and psychosocial history. Associations between IPI and the independent variables were assessed using chi-square analysis and analysis of variance. Multivariable multinomial logistic regression models examined significant associations while controlling for other independent variables and potential confounders. Results: Participants with current IPV were more likely to have a short IPI (odds ratio [OR]=13.1; 95% confidence interval [CI]=1.07?158.9; p=0.04) than healthy IPI. Women with family social support were more likely to have a healthy IPI (OR=5.88, 95% CI=1.02?31.25, p=0.05) than those without family social support. Maternal anxiety and depression did not significantly influence IPI. Conclusion: IPV increased the likelihood of having an unhealthy IPI among this population and family social support increased the likelihood of having a healthy IPI. Additional efforts to address IPV and enhance family social support may lead to improved pregnancy outcomes.